11C-Methionine-PET in Multiple Myeloma: A Combined Study from Two Different Institutions - Lapa, Constantin; Garcia-Velloso, Maria J; Lückerath, Katharina; Samnick, Samuel; Schreder, Martin; Otero, Paula Rodriguez; Schmid, Jan-Stefan; Herrmann, Ken; Knop, Stefan; Buck, Andreas K; Einsele, Hermann; San-Miguel, Jesus; et al. (Theranostics, 2017)
11C-methionine (MET) has recently emerged as an accurate marker of tumor burden and disease activity in patients with multiple myeloma (MM). This dual-center study aimed at further corroboration of the superiority of MET as positron emission tomography (PET) tracer for staging and re-staging MM, as compared to 18F-2`-deoxy-2`-fluoro-D-glucose (FDG). 78 patients with a history of solitary plasmacytoma (n=4), smoldering MM (SMM, n=5), and symptomatic MM (n=69) underwent both MET- and FDG-PET/computed tomography (CT) at the University Centers of Würzburg, Germany and Navarra, Spain. Scans were compared on a patient and on a lesion basis. Inter-reader agreement was also evaluated. In 2 patients, tumor biopsies for verification of discordant imaging results were available. MET-PET detected focal lesions (FL) in 59/78 subjects (75.6%), whereas FDG-PET/CT showed lesions in only 47 patients (60.3%; p<0.01), accordingly disease activity would have been missed in 12 patients. Directed biopsies of discordant results confirmed MET-PET/CT results in both cases. MET depicted more FL in 44 patients (56.4%; p<0.01), whereas in two patients (2/78), FDG proved superior. In the remainder (41.0%, 32/78), both tracers yielded comparable results. Inter-reader agreement for MET was higher than for FDG (κ = 0.82 vs κ = 0.72). This study demonstrates higher sensitivity of MET in comparison to standard FDG to detect intra- and extramedullary MM including histologic evidence of FDG-negative, viable disease exclusively detectable by MET-PET/CT. MET holds the potential to replace FDG as functional imaging standard for staging and re-staging of MM.11C-methionine (MET) has recently emerged as an accurate marker of tumor burden and disease activity in patients with multiple myeloma (MM). This dual-center study aimed at further corroboration of the superiority of MET as positron emission tomography (PET) tracer for staging and re-staging MM, as compared to 18F-2`-deoxy-2`-fluoro-D-glucose (FDG). 78 patients with a history of solitary plasmacytoma (n=4), smoldering MM (SMM, n=5), and symptomatic MM (n=69) underwent both MET- and FDG-PET/computed tomography (CT) at the University Centers of Würzburg, Germany and Navarra, Spain. Scans were compared on a patient and on a lesion basis. Inter-reader agreement was also evaluated. In 2 patients, tumor biopsies for verification of discordant imaging results were available. MET-PET detected focal lesions (FL) in 59/78 subjects (75.6%), whereas FDG-PET/CT showed lesions in only 47 patients (60.3%; p<0.01), accordingly disease activity would have been missed in 12 patients. Directed biopsies of discordant results confirmed MET-PET/CT results in both cases. MET depicted more FL in 44 patients (56.4%; p<0.01), whereas in two patients (2/78), FDG proved superior. In the remainder (41.0%, 32/78), both tracers yielded comparable results. Inter-reader agreement for MET was higher than for FDG (κ = 0.82 vs κ = 0.72). This study demonstrates higher sensitivity of MET in comparison to standard FDG to detect intra- and extramedullary MM including histologic evidence of FDG-negative, viable disease exclusively detectable by MET-PET/CT. MET holds the potential to replace FDG as functional imaging standard for staging and re-staging of MM.